Anwar returns the final twist : the prosecution and release of Anwar Ibrahim - Trowell, Mark (Marshall Cavendish Editions, 2018)
16 May 2018 : Anwar Ibrahim is released from prison and receives a full royal pardon from the King of Malaysia. This was an astonishing turn of events for the former Deputy Prime Minister who was serving a second prison term for sodomy, a charge that Anwar has always refuted. For Mark Trowell QC, who observed the criminal trials of Anwar Ibrahim, the release was as historic as the release of Nelson Mandela in South Africa. Read about the dramatic twists and turns in the prosecution of Anwar Ibrahim, from when he was first charged with sodomy in September 1998 to his vindication 20 years later. This book covers not only the trials and prosecution Anwar was subjected to and which led to the guilty verdict and sentence of fiveyears' imprisonment in February 2015, it also recounts the changing political tide sweeping through Malaysia that culminated in his historic release in 2018.